2021
DOI: 10.3928/01913913-20210614-03
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus as a Presenting Sign in Retinoblastoma

Abstract: To report the presenting signs of Retinoblastoma (Rb) in a large cohort of patients who underwent orthoptic assessment at presentation. METHODSA retrospective medical chart review of 131 patients with retinoblastoma who presented consecutively to a single institution over a 6-year period. The main outcome measure was the presenting sign(s) of the disease. RESULTSOf 131 Rb patients, 88 presented with unilateral disease and 43 bilateral disease (mean age; 22.7 and 14.8 months respectively). Leukocoria (L) was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The most common presentation in our patients was leukocoria followed by strabismus which are the two most common presenting complaints of RB documented in medical literature [10]. Genetic testing is a scant resource in the developing world, therefore, based on verbal con rmation during history taking, it was found that two patients (13.33%) had a positive family history for RB.…”
Section: Discussionmentioning
confidence: 67%
“…The most common presentation in our patients was leukocoria followed by strabismus which are the two most common presenting complaints of RB documented in medical literature [10]. Genetic testing is a scant resource in the developing world, therefore, based on verbal con rmation during history taking, it was found that two patients (13.33%) had a positive family history for RB.…”
Section: Discussionmentioning
confidence: 67%
“…A study from Chennai, India indicated that the majority of parents in that setting believed that strabismus was a sign of good fortune and did not seek care for [19]. Sometimes, strabismus can be the first sign of ocular tumor, like retinoblastoma [43]. Poor parental education, misunderstandings, and misinformation have a negative impact on the age of strabismus presentation and management, which differs from country to country [44].…”
Section: Action #2 Directly Address Common Misconceptions and Myths A...mentioning
confidence: 99%